A Review on Vocabulary Tests of High Frequency English Words - Phuong, Bui Thi Kim (VNU Journal of Science: Education Research, 2022)
Vocabulary assessment plays a ctitical role in language education for EFL learners, educators and researchers. The article introduces and analyzes four English receptive vocabulary tests of high frequency words, including Vocabulary Levels Test, Vocabulary Size Test, Computer Adaptive Test of Size and Strength and New General Service List Test. Based on the review of the four tests, it provides practical suggestions for choosing an appropriate test to assess the vocabulary knowledge of EFL learners in Vietnam as well as implications for building new vocabulary tests to meet the demand of English language teaching and learning practices as well as the research needs in the field of language education in Vietnam.